2019
DOI: 10.1111/cob.12313
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effect of chromium supplementation on anthropometric indices of subjects with overweight or obesity

Abstract: Summary The role of chromium as a weight loss agent remains questionable, and although previous meta‐analyses findings have reported small reductions in body weight in individuals with overweight/obesity following chromium supplementation, there have been significant limitations with these findings. The objective of this meta‐analysis was to evaluate the current evidence for the efficacy of oral chromium supplementation in individuals with overweight/obesity from randomized controlled trials. Studies were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Although the effectiveness and safety of chromium picolinate supplementation in overweight and obese people are controversial [ 96 , 97 ], patients with thyroid diseases may use chromium supplements to control body weight.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effectiveness and safety of chromium picolinate supplementation in overweight and obese people are controversial [ 96 , 97 ], patients with thyroid diseases may use chromium supplements to control body weight.…”
Section: Resultsmentioning
confidence: 99%
“…Chromium (III) or trivalent chromium is an essential trace element that plays a role in carbohydrate and lipid metabolism in the human body and it is normally present in blood and urine, with the mean level of 0.10–0.16 and 0.22 μg/L, respectively [ 58 ]. As mentioned before, Cr supplements could decrease BW and improve anthropometric indices in the obese but not an already-DM population [ 27 ]. Chronic exposure to Cr was found to decrease MetS development in the United States, but not in the Korean population [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were also some studies that focused on the association between heavy metals and body composition but more inconsistently. Chromium (Cr) supplementation was associated with mild bodyweight loss and a decrease in body fat percentage in obese or overweight participants [27]. Serum Zn concentrations were positively associated with both abdominal obesity and total body fat in men but not in women [28].…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 meta-analysis of randomized studies found that chromium supplementation resulted in only 0.5 kg additional weight reduction in subjects with overweight and obesity, as compared with those taking a placebo [110], and a comparable result (mean: 0.75 kg) was achieved in a similar 2019 meta-analysis [111]. In addition, the literature indicates that chromium supplementation may be associated with several side effects: emesis, nettlerash, and dizziness [112].…”
Section: Dietary Supplements and Weight Lossmentioning
confidence: 97%